Primary Mesenteric Sertoli-Leydig Cell Tumor: A Case Report and Review of the Literature - Trabelsi, Amel (Hindawi Publishing Corporation, 2008)
The occurrence of primary sex cord-stromal tumors at extraovarian sites is exceedingly rare. We report a new case of Sertoli-Leydig cell tumor in the mesentery of a 78-year-old woman who presented with occlusive syndrome and reviewed the previously reported cases of extraovarian sex cord-stromal tumors in the English literature.